Viral RNA Silencing Suppressors (RSS): Novel Strategy of Viruses to Ablate the Host RNA Interference (RNAi) Defense System - Bivalkar-Mehla, Shalmali (2010)
Pathogenic viruses have developed a molecular defense arsenal for their survival by counteracting the host anti-viral system known as RNA interference (RNAi). Cellular RNAi, in addition to regulating gene expression through microRNAs, also serves as a barrier against invasive foreign nucleic acids. RNAi is conserved across the biological species, including plants, animals and invertebrates. Viruses in turn, have evolved mechanisms that can counteract this anti-viral defense of the host. Recent studies of mammalian viruses exhibiting RNA silencing suppressor (RSS) activity have further advanced our understanding of RNAi in terms of host-virus interactions. Viral proteins and non-coding viral RNAs can inhibit the RNAi (miRNA/siRNA) pathway through different mechanisms. Mammalian viruses having dsRNA-binding regions and GW/WG motifs appear to have a high chance of conferring RSS activity. Although, RSSs of plant and invertebrate viruses have been well characterized, mammalian viral RSSs still need in-depth investigations to present the concrete evidences supporting their RNAi ablation characteristics. The information presented in this review together with any perspective research should help to predict and identify the RSS activity-endowed new viral proteins that could be the potential targets for designing novel anti-viral therapeutics.